Evaluating Hajj and Umrah Guide Certification as a Model of Da‘wah Education for Quality Assurance (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study evaluates the effectiveness of the Professional Hajj and Umrah Guide Certification Education and Training Program as a quality assurance mechanism for manasik guidance in Indonesia. The research responds to the critical need to ensure that guides possess not only administrative qualifications but also professional, pedagogical, and spiritual competencies amid the increasing complexity of Hajj management. Using a descriptive quantitative approach, data were collected from 374 program alumni through questionnaires, interviews, document analysis, and pre- and post-tests. The study applies a comprehensive evaluation framework integrating the CIPPO (Context, Input, Process, Product, Outcome) model with Kirkpatrick’s four-level evaluation (Reaction, Learning, Behavior, Result). Data analysis employed descriptive statistics, paired sample t-tests, and qualitative triangulation. Results indicate high relevance and effectiveness across all evaluation aspects. A significant improvement in participants’ competencies was confirmed by the paired sample t-test (t = -16.853; p < 0.05), despite a modest score increase due to rigorous assessment standards. Overall, the program effectively enhances the scientific, spiritual, and professional competence of certified guides and strengthens national quality assurance for Hajj and Umrah guidance services. Novelty: This study establishes a novel approach to Islamic education evaluation by successfully integrating the macro-level CIPPO framework with the micro-level Kirkpatrick model to assess professional da‘wah training. Unlike previous studies that focus purely on the administrative or theological aspects of Hajj, this research offers a new, standardized quality assurance paradigm that redefines Hajj and Umrah certification as a structured, measurable model of professional da‘wah education.